A translation of the structure of mussel byssal threads into synthetic materials by the utilization of histidine-rich block copolymers. Issue 25 (15th June 2018) - Enke, Marcel; Bose, Ranjita K.; Zechel, Stefan; Vitz, Jürgen; Deubler, Robert; Garcia, Santiago J.; van der Zwaag, Sybrand; Schacher, Felix H.; Hager, Martin D.; Schubert, Ulrich S.
Abstract : The self-healing capacities of mussel-inspired metallopolymers based on block copolymers containing histidine are briefly presented. Abstract : Mussel byssal threads are well-known due to their self-healing ability after the mechanical stress caused by waves. The proposed mechanism demonstrates the importance of reversible histidine–metal interactions as well as the block copolymer-like hierarchical architecture of the underlying protein structure. Taking these two aspects as inspiration for the design of synthetic analogs, different histidine-rich block copolymers were synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization. The hard domain was mimicked using polystyrene and the soft domain consists of n -butyl acrylate (BA) as well as histidine moieties as ligands. The block copolymers were crosslinked using different zinc(ii ) salts and the resulting metallopolymers were investigated with respect to their self-healing abilities. The observed two-step mechanism of the self-healing process was studied in detail. Furthermore, the mechanical properties were determined by nanoindentation and were correlated with other results.